PERAN GURU PAI DALAM MENGEMBANGKAN KECERDASAN EMOSIONAL DAN SPIRITUAL SISWA DI SMK NEGERI 1 SEMARANG - M Chovianan Al Sabah; Susiyanto Susiyanto (Universitas Islam Sultan Agung, 2019)
The purpose of this study was to determine how the role of Islamic religious education teachers in developing emotional intelligence and spiritual intelligence of students at SMK Negeri 1 Semarang. This type of research uses qualitative descriptive research so that the collection of data using observation, interviews, and documentation to the parties concerned. While the data analysis I use is qualitative data analysis which includes three aspects, namely: data reduction, data presentation, and drawing conclusions. The results showed that there were changes given by religious teachers to their students. Where religious teachers are able to develop between emotional intelligence and spiritual students. In addition to providing material, religious teachers also provide exemplary learning, direct their students to pray in congregation, and control the activities of their students both at school and at home.Keywords: Teacher Role, Emotional Intelligence, Spiritual Intelligence